(x – 2y)/3 = 1; 2x – 4y = 9/2

(v) (x – 2y)/3 = 1; 2x – 4y = 9/2

Sol. (x – 2y)/3 = 1
x – 2y = 3
Comparing with a1x + b1y = c1 we get, a1 = 1, b1 = – 2, c1 = 3

2x – 4y = 9/2
2 (2x – 4y) = 9
∴  4x – 8y = 9
Comparing with a2x + b2y = c2 we get, a2 = 4, b2 = – 8, c2 = 9

a1/a2 = 1/4 = 1/4 ............ eq. no. (i)
b1/b2 = -2/-8 = 1/4  ............ eq. no. (ii)
c1/c2 = 3/9 = 1/3 ............ eq. no. (iii)
From Equation (i) , (ii) and (iii) we get
a1/a2 = b1/b2  ≠  c1/c2


No solution.  

No comments:

Post a Comment